APPLICATION OF NEUTRON ACTIVATION ANALYSIS IN CHARACTERIZATION OF ENVIRONMENTAL SRM SAMPLES - Diah Dwiana Lestiani; Muhayatun Muhayatun; Natalia Adventini (Indonesian Journal of Chemistry, 2009)
Neutron activation analysis (NAA) is a nuclear technique that is excellent, multi-elemental, sensitive and has limit detection up to nanogram level. The application of NAA in analysis of Standard Reference Material (SRM) National Institute of Standard Technology (NIST) 1633b Coal Fly Ash and SRM NIST 1646a Estuarine Sediment was carried out for NAA laboratory inter-comparison program. The samples were distributed by Technology Centre for Nuclear Industry Material, National Nuclear Energy Agency as a coordinator of the inter-comparison program. The samples were irradiated in rabbit facility of G.A. Siwabessy reactor with neutron flux ~ 1013 n.cm-2.s-1, and counted with HPGe spectrometry gamma detector. Several trace elements in these samples were detected. The concentration of Al, Mg, K, Na and Ti in SRM NIST 1633b were 15.11, 7.35, 2.09, 0.192 and 0.756% respectively and the concentration of As, Cr, Mn, Se, V, Sb, Co, Cs, La, Sc and Sm were 137.0, 195.6, 129.4, 9.61, 305.8, 5.45, 56.2, 11.18, 83.73, 41.1 and 19.13 mg/kg respectively. The analysis result in SRM NIST 1646a of the concentration of Al and Na were 2.15 and 0.70% and the concentration of As, Cr, Co, La and Sc were 5.75, 36.3, 4.58, 15.67 and 4.00 mg/kg respectively. These results analysis had relative bias and u-test ranged from 0.4-11.3% and 0.15-2.25. The accuracy and precision evaluation based on International Atomic Energy Agency (IAEA) criteria was also applied. The result showed that NAA technique is applicable for the environmental samples analysis, and it also showed that the NAA laboratory in BATAN Bandung has a good performance.